Historical Perspectives on Score Comparability Issues Raised by Innovations in Testing. Issue 2 (11th May 2022) - Baldwin, Peter; Clauser, Brian E.
Abstract: While score comparability across test forms typically relies on common (or randomly equivalent) examinees or items, innovations in item formats, test delivery, and efforts to extend the range of score interpretation may require a special data collection before examinees or items can be used in this way—or may be incompatible with common examinee or item designs altogether. When comparisons are necessary under these nonroutine conditions, forms still must be connected by something and this article focuses on these form‐invariant connective somethings . A conceptual framework for thinking about the problem of score comparability in this way is given followed by a description of three classes of connectives. Examples from the history of innovations in testing are given for each class.